Designing a Future Study Model: Examining Bank Employees’ Attitudes Towards Job Security in the Era of Blockchain Technology (Horizon 2031) - Saeid Ghazi Nezhad; Hasan Darvish; Mohammad Mahmoudi Meymand (Journal of Asset Management and Financing)
Blockchain technology has emerged as a crucial factor impacting the banking sector. This study aimed to design and elucidate a future research model that explored bank employees’ attitudes towards job security in the context of blockchain technology by the year 2031. Through a comprehensive review of relevant studies, this research identified the future research factors and drivers that influenced bank employees’ attitudes regarding job security in the face of blockchain technology. Indicators were identified and subjected to coding and theming processes. The dimensions and indicators were then selected based on expert opinions and distributed in a questionnaire format. Subsequently, a self-interaction matrix, initial achievement matrix, and final achievement matrix were developed followed by dimension leveling and model presentation. The key factors in the model encompassed the employees' understanding of usefulness and ease of use, behavioral intentions, beliefs, norms, values, and organizational culture, provision and updating of infrastructure, cost considerations, financial and banking market structure, technical challenges, and the benefits associated with blockchain technology.Keywords: Blockchain, Employee’s Attitude, Job Security, Benefits of Blockchain  IntroductionThe monetary-financial system today operates within a complex and interconnected structure, involving multiple actors, varying levels of trust, and continuous information flows. However, this current structure has gradually experienced a decline in reliability, efficiency, transparency, and certainty over time. While the use of technology in financial services is not a new phenomenon, recent years have witnessed a remarkable transformation in the provision of financial services due to the integration of advanced technologies, such as the Internet of Things, artificial intelligence, and blockchain (Edwards et al., 2019).Adoption and development of blockchain and distributed ledger technology in the banking industry are still in the early stages, encountering several challenges along the way. Nevertheless, industry experts anticipate that this innovation holds significant potential to create new opportunities across various banking domains. Rapid evolution and introduction of new concepts within blockchain technology make it challenging to discern its specific features and characteristics (Carson et al., 2018).In tandem with digitization of banking services and growth of electronic and digital banking, financial institutions are grappling with excess human resources and seeking ways to reduce financial costs. According to the 1401 financial statements of banks, the number of bank employees in Iran has increased from 34,076 to 32,470 (Ebrahimian & Mirsepasi, 2017). Against this backdrop, the present research aimed to design and elucidate a future study model that could explore employees' attitudes towards job security in the face of blockchain technology by the year 2031. This investigation held significant importance and necessity from multiple perspectives, particularly considering that blockchain is a relatively new field in Iran with limited prior research. The existing studies on blockchain have predominantly focused on theoretical descriptions rather than practical applications.Materials & MethodsThe future study factors and drivers influencing bank employees’ attitudes towards job security in the context of blockchain technology by the year 2031 were identified based on the existing studies. Following identification of indicators, a coding and theming process was undertaken, utilizing the symbols EP for foreign articles and FP for Persian articles. Factors and drivers were then coded and themed based on expert opinions and the indicators and dimensions were subsequently selected.The expert panel for this study comprised banking executives, academic experts, and managers with notable qualifications. These individuals possessed relevant experience, having served as deputy or chief managers in banks and financial institutions or had a minimum of 4 years of teaching experience as university faculty members. In addition, bank managers and consultants with at least 10 years of industry experience were included. Selection of the 16 experts was based on theoretical saturation. The dimensions derived from the coding and theming processes were distributed among the experts in the form of a questionnaire.The experts were selected using the judgment method, resulting in a panel of 16 individuals. Subsequently, the self-interaction matrix, initial achievement matrix, and final achievement matrix were determined to facilitate dimension leveling. The initial model underwent a thorough review and revision, taking into account the background information and logical reasoning. Research FindingsTo identify the factors influencing the bank employees’ attitudes towards job security in the face of blockchain technology on the horizon of 2031, the following steps were undertaken: 1) Research question formulation: The research questions were developed in line with the main objective of the study. They aimed to explore the dimensions and indicators necessary to identify the factors affecting bank employees' attitudes towards job security in the context of blockchain technology by the year 2031. 2) Literature search: A comprehensive search was conducted to gather relevant domestic and international scholarly articles and books. Keywords, such as "blockchain in the horizon of 2031", "job security", and "blockchain adoption", were utilized to identify authoritative sources. 3) Research content analysis: The directed content analysis technique, specifically the directed approach, was employed in this research. 4) Coding process: After collecting the articles and books, an open coding process was employed. Latin articles were indexed with the symbol EP, while Persian articles were indexed with the symbol FP. The numbers assigned during the coding process indicated the number of articles. The coded data were then categorized into themes. This categorization was done within the framework of potential themes, resulting in the establishment of 11 themes. It is important to note that the identification of these 11 themes was the result of an iterative process over an extended period with validation from experts. 5) Determination of the levels of indicators: To prioritize the variables, separate sets were established for the achieving the predecessor of each variable. The attainable set represented the set of values, where the numerical value in the rows of the matrix was 1, while the predecessor set indicated the columns marked as 1. By intersecting these two sets, a common set was obtained. The variables that matched between the common set and the attainable set were considered priorities. These variables were then removed from the table and the process was repeated with the remaining variables to generate subsequent tables. This process continued until the priorities of all variables were determined. Discussion & ConclusionIn this study, the key drivers were extracted and classified using the qualitative content analysis method and incorporating expert opinions. Drawing upon the obtained results and comparison with other studies, the following suggestions are presented: 1) Bank managers should explore the theoretical and practical benefits of blockchain technology both globally and within Iran. This knowledge will enable them to understand the advantages, not only for bank employees, but also for the bank itself, society, and other stakeholders. 2) Bank managers should educate bank employees about the benefits of blockchain technology by creating educational content and disseminating it through online platforms and social campaigns. 3) Bank managers should deepen their understanding of the nature and characteristics of blockchain technology, particularly in terms of security and reliability. 4) Given that employee trust in blockchain technology significantly influences their behavior, it is advisable to examine the results of tests and experimental implementations conducted worldwide to assess the technology's security. This information can also be utilized to enhance employee trust in blockchain. 5) Managers and bank officials, who intend to adopt blockchain technology, should collaborate with prominent universities and professors to conduct challenges and evaluations. These initiatives should address any uncertainties, potential security issues, and theoretical and practical concerns, thereby fostering higher levels of user trust.Bank officials should establish support mechanisms for bank employees by forming joint working groups and evaluating the necessary infrastructure for blockchain implementation.Bank managers should prioritize the potential of emerging technologies, such as blockchain, and take steps towards their adoption. Considering the benefits observed in other industries and countries, managers should strive to create favorable conditions for incorporating blockchain technology within their organizations. This can begin by providing free educational resources about blockchain technology to the employees, exploring its motivations and benefits and considering its strengths and limitations through the SWOT matrix. By doing so, they can harness the advantages of blockchain technology, seize opportunities, and mitigate potential threats and resistance.Given the ongoing digitization of the financial market, managers should consider implementing blockchain technology on a trial basis. The decision to fully adopt the technology should be based on the results and advantages derived from the trial period.Considering the impacts of blockchain adoption factors on employees' attitudes, managers should give special attention to these factors and strengthen the necessary infrastructure for successful implementation.Adequate investment should be made in training employees to enhance their understanding, attitude, acceptance, and application of blockchain technology within the bank.Organizing training workshops for employees and encouraging them to acquire skills related to blockchain technology, as well as improving management and information skills, is highly recommended.Investing in employees to increase their understanding and application of blockchain technology should be prioritized.